Life‐history strategy varies with the strength of competition in a food‐limited ungulate population. (23rd February 2020) - Kentie, Rosemarie; Clegg, Sonya M.; Tuljapurkar, Shripad; Gaillard, Jean‐Michel; Coulson, Tim
Abstract: Fluctuating population density in stochastic environments can contribute to maintain life‐history variation within populations via density‐dependent selection. We used individual‐based data from a population of Soay sheep to examine variation in life‐history strategies at high and low population density. We incorporated life‐history trade‐offs among survival, reproduction and body mass growth into structured population models and found support for the prediction that different life‐history strategies are optimal at low and high population densities. Shorter generation times and lower asymptotic body mass were selected for in high‐density environments even though heavier individuals had higher probabilities to survive and reproduce. In contrast, greater asymptotic body mass and longer generation times were optimal at low population density. If populations fluctuate between high density when resources are scarce, and low densities when they are abundant, the variation in density will generate fluctuating selection for different life‐history strategies, that could act to maintain life‐history variation. Abstract : In this paper, we demonstrate that fluctuating population densities could contribute to the maintenance of variation in life-history strategies within a population. We used individual-based data from a population of Soay sheep and incorporated life-history trade-offs into structured population models. Our work provides a way to extend research to observational field studies to examine selection on life-history strategies.